INCLUSIVE ISLAMIC EDUCATION MODEL BASED ON COMMUNITY ORGANIZATIONS: A STUDY ON THE DIAN INTERFIDEI COMMUNITY IN YOGYAKARTA - Madum, Mohamad (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Inclusive education is an approach that supports the recognition of diversity, especially in the context of religiosity. The inclusive Islamic education model is relevant in responding to the challenges of diversity in Indonesia, especially in a pluralistic society. This study examines the inclusive Islamic education model based on community organizations by studying the DIAN Interfidei Community in Yogyakarta. This research method uses qualitative data collection techniques: in-depth interviews, participatory observation, and document analysis. The study results indicate that the Dian Interfidei Community developed an inclusive education model through programs prioritizing interfaith dialogue, tolerance, and respect for differences. Islamic education based on community organizations such as that carried out by DIAN Interfidei can be a strategic alternative in promoting the values of inclusivity and tolerance in Indonesia. The implementation at the implementation stage has been by the logical framework, namely encouraging dialogue between religion and politics, encouraging interfaith relations to develop in Indonesia (collaboration with interfaith communities, educational institutions and government institutions), Financing the establishment of interfaith schools (SLI), and Building interfaith awareness through social activities